2003
DOI: 10.1161/01.atv.0000097783.01596.e2
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic Plaque Rupture

Abstract: Abstract-It is generally established that the unstable plaque is the major cause of acute clinical sequelae of atherosclerosis.Unfortunately, terms indicating lesions prone to plaque instability, such as "vulnerable plaque," and the different phenotypes of unstable plaques, such as plaque rupture, plaque fissuring, intraplaque hemorrhage, and erosion, are often used interchangeably. Moreover, the different phenotypes of the unstable plaque are mostly referred to as plaque rupture.In the first part of this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
1
4

Year Published

2003
2003
2015
2015

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 138 publications
(50 citation statements)
references
References 133 publications
0
43
1
4
Order By: Relevance
“…Intraplaque hemorrhages are considered prominent markers of plaque instability. 11,18,23,24 Without angiotensin II stimulation, the more extensive lesions that developed in the lowered shear stress regions showed small intraplaque hemorrhages close to the internal elastic lamina in 28% of the treated animals. Hemorrhages were never observed in the lesions in oscillatory shear stress regions.…”
Section: Cheng Et Al Shear Stress and Atherosclerosis 2749mentioning
confidence: 97%
See 2 more Smart Citations
“…Intraplaque hemorrhages are considered prominent markers of plaque instability. 11,18,23,24 Without angiotensin II stimulation, the more extensive lesions that developed in the lowered shear stress regions showed small intraplaque hemorrhages close to the internal elastic lamina in 28% of the treated animals. Hemorrhages were never observed in the lesions in oscillatory shear stress regions.…”
Section: Cheng Et Al Shear Stress and Atherosclerosis 2749mentioning
confidence: 97%
“…Morphologically, the destabilizing components accumulate in pools underneath a thin, fibrous cap, with little infiltration of vascular smooth muscle cells. 17,18 Shear stress could determine the vulnerability of the lesion by altering the gene expression of endothelial cells (eg, upregulation of adhesion molecules, proinflammatory factors, and factors that mediate vascular wall permeability) and by increasing the interaction of proatherogenic components in the blood (lipoproteins and monocytes) with the activated endothelium. 19 -21 We found that lowered shear stress lesions contained more lipids, fewer vascular smooth muscle cells, and less collagen compared with lesions in the oscillatory shear stress region.…”
Section: Cheng Et Al Shear Stress and Atherosclerosis 2749mentioning
confidence: 99%
See 1 more Smart Citation
“…Research, including our previous studies, also shows that the symptomatic nature of carotid atherosclerotic plaques is rather an outcome of a combined effect of numerous, both intra-and extravascular factors [10,14]. CD4 + CD28 -Lc could have been only one of such factors by their involvement in the process of plaque destabilization.…”
Section: Discussionmentioning
confidence: 79%
“…Plak rüptürü, fissür plak, plak içi kanama ve erozyon unstable plakların farklı fenotipleri olup "hassas plak" gibi plak instabilitesine eğilimli lezyonları tanımlamakta ve maalesef terim olarak çoğunlukla birbirinin yerine kullanılmaktadır. Ayrıca, unstable plakların farklı fenotipleri ço-ğunlukla plak rüptürü olarak adlandırılır [15].…”
unclassified